The Use of Big Data and Business Intelligence in Management Accounting Decision Making - Narulita, Friska Dhea; Baderi, Rahmawati Nur; Hidayati, Cholis (Journal of Advances in Accounting, Economics, and Management, 2025)
Digital transformation drives a paradigm shift in management accounting, where Big Data and Business Intelligence (BI) now play a strategic role in supporting data-based decision making. This article aims to comprehensively examine how the integration of the two technologies improves the effectiveness, speed, and accuracy of the managerial accounting process. The method used is a literature study with a descriptive qualitative approach, reviewing accredited scientific publications for the 2020–2025 period. The results of the study show that Big Data provides real-time data volume and diversity (5V), while BI processes raw data into interactive and predictive visual information that supports budgeting, forecasting, and what-if analysis. The synergy of the two allows for more timely anomaly detection, performance prediction, and strategic recommendations, while minimizing the risk of human error. On the other hand, the implementation of Big Data and BI faces significant challenges related to IT infrastructure, Human Resource competency, system integration, and data security and governance. To that end, organizations need to prepare a digital roadmap that includes HR training, information system audits, and data protection policies, supported by top management commitment and long-term investment. In conclusion, the combination of Big Data and BI is not just a technical tool, but a strategic pillar that transforms management accounting into a proactive, predictive, and value-added function for companies in the digital era.